Muscle-specific programmed cell death 5 deletion attenuates cardiac aging. (15th December 2021) - Naz, Amber; Zhang, Shasha; An, Lin; Song, Zongpei; Zi, Zhenguo; Wu, Jian; Lai, Shuaiwei; Mazhar, Haniya; Xu, Mingqing; Chen, Yingyu; Zou, Yunzeng; He, Lin; et al.
Abstract: Programmed cell death 5 (PDCD5) is a tumor suppressor gene that regulates the cell cycle, apoptosis and immune responses. However, the physiological function of Pdcd5 in cardiac aging remains unknown. We find that Pdcd5 mRNA and protein levels were significantly increased in the heart of mice with age. Therefore, we hypothesize that Pdcd5 regulates cardiac aging. To test the hypothesis, we generated muscle-specific Pdcd5 -deficient mice. Mature adult Pdcd5 -deficient mice had normal cardiac morphology and function. In naturally aged mice, Pdcd5 deficiency alleviated age-related cardiac phenotypes including reduced fibrosis and suppressed cardiomyocyte hypertrophy. Moreover, muscle-specific Pdcd5 deficiency attenuated cellular senescence in the heart as demonstrated by decreased number of senescence-associated β-galactosidase-positive cells, diminished p53, p21 and p16 expression, and reduced the senescence-associated secretory phenotype. Apoptotic cell death was reduced by Pdcd5 deficiency in the heart as revealed by terminal deoxynucleotidyl transferase dUTP nick end labeling assay, which was coincident with diminished Bcl-2-associated X protein, and enhanced B-cell lymphoma 2 and X-linked inhibitor of apoptosis protein expression. Mitochondrial quality in cardiomyocytes was improved by Pdcd5 deficiency through increased Parkin-mediated mitophagy. In addition, Pdcd5 deficiency alleviated doxorubicin-induced premature cellular senescence and cardiac aging. Furthermore, Pdcd5 protein abundance was significantly correlated with p53 protein abundance, and Pdcd5 interacted with p53 in the heart. Taken together, our results reveal that Pdcd5 deficiency attenuates cardiac aging by reducing cellular senescence and apoptosis, and increasing Parkin-mediated mitophagy, likely through p53. Pdcd5 is a novel regulator of cardiac aging and a potential therapeutic target. Highlights: Muscle-specific Pdcd5 deficiency attenuates natural cardiac aging and doxorubicin-induced premature cardiac aging. Pdcd5 deficiency reduces cellular senescence and apoptosis, and increases Parkin-mediated mitophagy in aged heart. Pdcd5 protein abundance is significantly correlated with p53 protein abundance, and Pdcd5 interacts with p53 in the heart.